The Effect of Tub Bathing on Body Temperature in Preterm Infants: Randomized Clinical Trial - Mahnaz Jabraeili; Alehe Seyed rasooli; Seyed Mohammad Bagher Seyed Hosseini; Morteza Ghojazadeh; Ameneh Safaei (Mashhad University of Medical Sciences, 2015)
Background: Bathing of a premature newborn is important in care giving, but due to inadequate evidences, infant caregivers are not sure about bathing being safe in terms of not causing hypothermia and are not systematically considered in the infants' care giving programs. Aim: To determine the effect of tub bathing on body temperature of preterm infants". Methods: This study is a randomized controlled clinical trial which was conducted in 1392 in neonatal unit of Al-zahra hospital. 118 preterm infants were randomly divided into intervention and control groups. The infants in the control group received routine skin care only. The intervention group was bathed three times every other day inside the bathtub. In both group, the infants' body temperature was measured at the same times by the researcher. Data were analyzed with SPSS software version 14 using independent T-test, Chi-square and repeated measurements tests. Results: In both groups, boys outnumbered girls. At the time of inclusion, the infants' age was 5.8 ± 8.6 days and their weight was 320.6 ± 1660.0 grams. In both groups, the mean temperature of premature infants after bath was dropped in all three times. Which was statistically significant in the first and second baths (P